2010
DOI: 10.1016/j.seizure.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and attitudes towards epilepsy among rural populations in East Coast Peninsular Malaysia: A preliminary exploration

Abstract: This study was carried out to gauge the preliminary insight regarding epilepsy among the rural society. The purposes of this study were: (1) to determine general level of awareness, knowledge and attitudes (AKA) towards epilepsy among rural communities, (2) to compare the AKA level based on socio-demographic characteristics and (3) to investigate rural cohort's perception of the best epilepsy treatment, preference for epilepsy information delivery and preference for mode of transportation to seek medical treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 26 publications
7
38
2
2
Order By: Relevance
“…This was relatively higher to those reported among general population from India, Malaysia, and Pakistan. 11,19,20 For the question "do you think epilepsy is contagious?" our results were better than the other Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was relatively higher to those reported among general population from India, Malaysia, and Pakistan. 11,19,20 For the question "do you think epilepsy is contagious?" our results were better than the other Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, large portions of people with epilepsy (PWE) go untreated or undertreated in the developing world [2]. Reasons for the treatment gap are varied and include a lack of antiepileptic drugs (AEDs), a lack of knowledge about epilepsy, poor prioritization, and health-care systems that are not well structured or too expensive [3][4][5][6]. Antiepileptic drugs can also be too expensive for those in poor regions, and cultural beliefs can be an impediment to proper treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These findings collaborated with studies in Malaysia, which showed that a higher level of education correlated positively with awareness, knowledge and attitudes concerning epilepsy. 14,15 Similarly, community-based studies have also reported that better-educated individuals offer more favourable opinions and display more positive attitudes towards people with epilepsy. 16,17 Previous studies have shown the impact of intervention course on the various domains of epilepsy.…”
Section: Discussionmentioning
confidence: 99%